Brain Tumor Diagnosis Using Machine Learning, Convolutional Neural Networks, Capsule Neural Networks and Vision Transformers, Applied to MRI - Akinyelu, Andronicus A. (2022)
Akinyelu, A. A., Zaccagna, F., Grist, J. T., Castelli, M., & Rundo, L. (2022). Brain Tumor Diagnosis Using Machine Learning, Convolutional Neural Networks, Capsule Neural Networks and Vision Transformers, Applied to MRI: A Survey. Journal of Imaging, 8(8), 1-40. [205]. https://doi.org/10.3390/jimaging8080205 -------------- Funding: We gratefully acknowledge financial support from FCT Fundação para a Ciência e a Tecnologia (Portugal), national funding through research grant Information Management Research Center—MagIC/NOVA IMS (UIDB/04152/2020).